A mild and efficient approach to the 6H-oxazolo[3, 2-f]pyrimidine-5, 7-dione scaffold via unexpected rearrangement of 2, 3-dihydropyrimido[6, 1-b][1, 5, 3]dioxazepine-7, 9(5H, 8H)-diones: synthesis, crystallographic studies, and cytotoxic activity screening. Issue 7 (17th February 2016) - Mieczkowski, Adam; Bazlekowa, Milena; Bagiński, Maciej; Wójcik, Jacek; Winczura, Alicja; Miazga, Agnieszka; Shahmoradi Ghahe, Somayeh; Gajda, Roman; Woźniak, Krzysztof; Tudek, Barbara
Graphical abstract: Abstract: We report a mild and efficient approach to the optically pure 6 H -oxazolo[3, 2- f ]pyrimidine-5, 7-dione scaffold via the unexpected rearrangement and ring contraction of 2, 3-dihydropyrimido[6, 1 -b ][1, 5, 3]dioxazepine-7, 9(5 H, 8 H )-diones derived from nucleoside precursors. The developed procedure enables the synthesis of a wide range of compounds with great structural diversity. The structure of the obtained compounds was confirmed by NMR spectroscopy and single crystal X-ray structural analysis. The final products were tested for cytotoxic effect on one non-cancerous (fibroblasts) and six cancer cell lines of different origins (colon, glioma, breast, cervix, vulvar, and lung). The synthesized products are low molecular weight compounds with lead-like properties suitable for a medicinal chemistry optimization program.